Rush - Silver, Eve. (New York : Katherine Tegen Books, 2013)
Rochester, New York, high schooler Miki Jones is pulled into a sort of a game in which she and other teens battle real-life aliens and the consequences of each battle could be deadly.
Keywords: Combat -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Science fiction; Combat -- Fiction; Extraterrestrial beings -- Fiction; Interpersonal relations -- Fiction